Choreographing coexistence: dance as a dialogic medium in multicultural counseling for youth - Nursilah Nursilah (Jurnal Konseling dan Pendidikan, 2025)
This study explores how dance can be integrated into a multicultural counseling approach to foster appreciation of cultural diversity among secondary school students in Jakarta, Indonesia. The research responds to increasing social fragmentation and identity tensions in urban multicultural contexts. This study employed a qualitative exploratory case study design conducted in three multicultural secondary schools in Jakarta. Participants included 15 students actively involved in dance and counseling sessions, 3 school counselors, 3 dance teachers, and 1 vice principal. Data were collected through in-depth interviews and participatory observation during cross-cultural dance practices and art-based group counseling sessions. Data were analyzed using thematic analysis following Braun and Clarke’s six-stage framework. The findings reveal three central themes. First, dance functions as an embodied learning medium that facilitates cultural self-awareness and identity validation. Second, collaborative cross-cultural dance activities reduce cultural stereotypes and promote empathy through shared movement experiences. Third, reflective group counseling sessions strengthen emotional openness, intercultural dialogue, and social solidarity among students. However, implementation challenges include limited counselor training in arts-based approaches and institutional perceptions that position arts as non-priority activities. The integration of dance into multicultural counseling offers a pedagogical and therapeutic model that supports identity development, empathy formation, and intercultural understanding in urban school settings. This study contributes to the advancement of arts-based multicultural counseling practices within pluralistic educational environments.